Distribution map of Ambrosia artemisiifolia L. (Asteraceae) in Italy. (4th May 2017) - Gentili, R.; Gilardelli, F.; Bona, E.; Prosser, F.; Selvaggi, A.; Alessandrini, A.; Martini, F.; Nimis, P. L.; Wilhalm, T.; Adorni, M.; Ardenghi, N. M. G.; Barni, E.; et al.
Abstract: The spread of the invasive and allergenic Ambrosia artemisiifolia L. in Italy was analysed and mapped using distribution data from a wide range of sources. Ambrosia artemisiifolia occupies 1057 floristic quadrants which are mostly distributed in the Po plain. The distribution obtained represents the basis to implement urgent management strategies.